2020
DOI: 10.1364/oe.396788
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the light extraction efficiency of AlInN nanowire ultraviolet light-emitting diodes with photonic crystal structures

Abstract: In this paper, AlInN nanowire ultraviolet light-emitting diodes (LEDs) with emission at ∼299 nm have been successfully demonstrated. We have further studied the light extraction properties of these nanowire LEDs using photonic crystal structures with square and hexagonal lattices of nanowires. The light extraction efficiency (LEE) of the periodic nanowire LED arrays was found to be significantly increased as compared to random nanowire LEDs. The LEEs reach ∼ 56%, and ∼ 63% for the square and hexagonal photonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Similarly, Jain et al. investigated and reported a square and hexagonal nanowire lattice PC structure to improve the LEE of AllnN nanowire UV LEDs 111 . This nanowire structure and lattice arrangement are shown in Figure 34A, and it is observed in Figure 34B that the LEE of square and hexagonal arrays could reach 56% and 63%, respectively, exhibiting higher LEE.…”
Section: Different Phc Structures To Improve the Optoelectronic Perfo...mentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, Jain et al. investigated and reported a square and hexagonal nanowire lattice PC structure to improve the LEE of AllnN nanowire UV LEDs 111 . This nanowire structure and lattice arrangement are shown in Figure 34A, and it is observed in Figure 34B that the LEE of square and hexagonal arrays could reach 56% and 63%, respectively, exhibiting higher LEE.…”
Section: Different Phc Structures To Improve the Optoelectronic Perfo...mentioning
confidence: 82%
“…Similarly, Jain et al investigated and reported a square and hexagonal nanowire lattice PC structure to improve the LEE of AllnN nanowire UV LEDs. 111 This nanowire structure and lattice arrangement are shown in Figure 34A, and it is observed in Figure 34B that the LEE of square and hexagonal arrays could reach 56% and 63%, respectively, exhibiting higher LEE. Li et al studied and reported a structure with a hexagonal array of nanopillar PC embedded into an InGaN/GaN LED, effectively improving the LED optical properties and demonstrating that the emission wavelength of the embedded PC LED was almost independent of the injection current.…”
Section: 22mentioning
confidence: 92%
See 1 more Smart Citation
“…Photonic crystals (PhCs), which are periodic dielectric modulations at wavelength-scale, have already been widely applied to enhance LEE in high refractive-index materials. [14][15][16][17] In addition, it has also been shown that they could exhibit strong interaction with guided Bloch modes when combined with thin-film devices, which could lead to very short extraction lengths. 18 In a recent study, our group has reported on the first PhC based AlGaInP/InGaP MQW CC fully optimized for blue-to-red and green-to-red color conversions in microdisplays.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, gallium nitride (GaN) nanowires have been investigated heavily in the past, due to the possibility of forming GaN nanowires on a wide range of substrates . Moreover, they are important “seeding” layers for the fabrication of scalable InGaN nanowire visible and AlGaN nanowire deep ultraviolet photonic devices at a wafer scale. Furthermore, GaN nanowires by selective area epitaxy (SAE) bring additional benefits and novel device developments, such as improving the light extraction efficiency of light emitting devices, novel photonic crystal lasers, and single photon sources, , due to the control on the nanowire formation site and size.…”
mentioning
confidence: 99%